Disain Model Samba Primary Domain Controller (PDC) Sebagai Network Drive Pada Laboratorium Jaringan Komputer - Molavi Arman; Meiriyama Meiriyama (UNIVERSITAS INDO GLOBAL MANDIRI)
Many institutions and companies such as educational institutions and private sector or government find obstacles with file storage problems. Current development requires institutions or companies to archive all events in the form of videos, documents, or images. What often happens is that many institutions still use conventional method of storage even though computer has been used. Besides they also do not have authorization about who could access the documents. Digital documents could be stored and accessed easily if the media of the document storage service is centralized. Companies or institutions usually share or send file documents in the workplace via email which highly depends on the file size limit and capacity and bandwidth resource, making it less effective for files with large amounts and files reaching gigabytes. One solution to cope with the problems is by designing and building centralized document sharing system using SAMBA protocol with Primary Domain Controller (PDC) and operating system using Linux Debian 9.4. File sharing system could only be accessed locally by applying profile for each user and password in the form of network drive so that file storage and access is more secure and faster since file document do not pass through the internet network. It could also reduce computer workload in terms of storage resources. Keywords: samba, primary domain controller , linux debian, network drive.